Antimicrobial Resistance Profile of MDR & Non-MDR Meropenem-Resistant Pseudomonas aeruginosa Isolates of Patients in Intensive Care Unit of Tertiary Hospital - Lameng, Imaculata Sonia Vidaryo; Budayanti, Ni Nyoman Sri; Prilandari, Luh Inta; Adhiputra, I Ketut Agus Indra (Indonesian Journal of Tropical and Infectious Disease, 2021)
Pseudomonas aeruginosa is one of the gram-negative bacteria that causes infection in the Intensive Care Unit (ICU) which is easily resistant. Patients infected with carbapenem-resistant P. aeruginosa are predicted to have a poor prognosis. This study aims to know the resistance profile of meropenem-resistant P. aeruginosa in the ICU. The results of this study can be used as a measure on the success of antimicrobial resistance control, infection control programs and become a reference for empirical therapy in the ICU. This study used a cross-sectional retrospective descriptive research method and was carried out at the Clinical Microbiology Laboratory of Sanglah Hospital Denpasar for three years, from 2018 to 2020. The results showed 38 of the 93 isolates of P. aeruginosa in the ICU were resistant to meropenem and were derived from sputum and urine. The percentage of meropenem-resistant P. aeruginosa isolates was higher in the multi-drug-resistant group and mostly came from sputum specimens. In 2018, Non-MDR meropenem-resistant P. aeruginosa isolates was that 100% sensitive to all other antibiotics used to treat P. aeruginosa infections, including; ceftazidime, cefepime, ciprofloxacin, gentamicin, amikacin, and piperacillin-tazobactam. In 2019 no meropenem-resistant P. aeruginosa isolates were found. In 2020, its sensitivity to antibiotics ceftazidime and piperacillin-tazobactam was 20.0%, ciprofloxacin 60.0% and to antibiotics gentamicin and amikacin 100%. MDR meropenem-resistant P. aeruginosa isolates in 2018 were still sensitive to ceftazidime (15.4%) and amikacin (69.2%) antibiotics, while in 2019 they were only sensitive to amikacin (37.5%). In 2020, P. aeruginosa isolates were sensitive to the antibiotics ceftazidime and cefepime (11.1%), piperacillin-tazobactam (22.2%), and amikacin (88.9%). Amikacin may be the choice of treatment for MDR meropenem-resistant P. aeruginosa.